The Draft Local Ordinance Review Process of the Local Council According to the Local Ordinance Initiative Process Act, B.E. 2565 (2022) - kwanraun, waraporn (Journal of Law and Political Affairs, 2025)
This research aims to study and analyze the deliberation process of local councils regarding draft local ordinances proposed by eligible voters in accordance with the Local Ordinance Initiative Process Act, B.E. 2565 (2022). The study was conducted through document analysis, including relevant concepts, theories, and legal provisions. The research findings revealed that The proposal of local ordinances can be initiated by local council members, local executives, and eligible voters within the jurisdiction of local administrative organization. All proposed local ordinances must be submitted for review by the local council, following the procedures outlined in the local council meeting regulations. For the local ordinances proposed by eligible voters according to the Local Ordinance Initiative Process Act, B.E. 2565 (2022), although the review process follows the same regulations as those proposed by local council members and local executives, there are key differences. These include allowing citizens to propose both general ordinances and budget-related ordinances with certification from the local executive, the appointment of an ad hoc committee comprising representatives of the petitioners to review the proposed ordinance, and the requirement that the local council must complete the review within sixty days from the date of receiving the draft ordinance. Additionally, if a draft ordinance is dismissed due to the expiration or dissolution of the local council, representatives of the petitioners can request its reconsideration. These provisions reflect the fundamental principles governing the review process for the local ordinances proposed by eligible voters. They align with the principles set forth in the Constitution of the Kingdom of Thailand, to ensure that local citizens can actively participate in local governance within the framework of a democratic system.